2020
DOI: 10.3390/molecules25235734
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bioactive Compounds of Opuntia ficus-indica (L.) Mill. Seeds from Spanish Cultivars

Abstract: Opuntia ficus-indica (L.) Mill. is the Cactaceae plant with the greatest economic relevance in the world. It can be used for medicinal purposes, animal nutrition, production of biofuels and phytoremediation of soils. Due to its high content of bioactive compounds, the prickly pear has antioxidant, antimicrobial and anticancer properties. The aim of this study was to determine the polyphenolic, fatty acid and amino acid profile and characterize the antioxidant capacity of seeds of seven Spanish prickly pear cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…In addition, almost all of the phenolic acids found in Opuntia stricta var. Dillenii fruit samples in the present study were previously reported for different authors in Opuntia ficus-indica cladodes [24], fruit juices [25], and seeds [26].…”
Section: Phenolic Compounds In Opuntia Stricta Var Dillenii Samplessupporting
confidence: 76%
“…In addition, almost all of the phenolic acids found in Opuntia stricta var. Dillenii fruit samples in the present study were previously reported for different authors in Opuntia ficus-indica cladodes [24], fruit juices [25], and seeds [26].…”
Section: Phenolic Compounds In Opuntia Stricta Var Dillenii Samplessupporting
confidence: 76%
“…In addition, oil yield varies depending on prickly pear varieties and locations. Kolniak-Ostek et al [ 23 ] found that the PPSO yield extracted from seeds of seven Spanish prickly pear cultivars, with diethyl ether using Soxhlet apparatus for 3 h, varied from 2.61% for “Nalle” to 7.69% for “Nopal ovalado”. In this line, the PPSO yield was found to be 5.4–9.9 g/100 g when the oil was extracted from 17 different origins in Morocco with n -hexane for 8 h using the Soxhlet apparatus [ 4 ].…”
Section: Prickly Pear Seed Oil Extraction and Yieldmentioning
confidence: 99%
“…Moreover, differences were found in the oil composition of the PPSO derived from various places. In this context, the fatty acids analysis of PPSO extracted from seven Spanish prickly pear cultivars showed differences between fatty acid content in different varieties, which were attributed to genetic factors [ 23 ]. The major fatty acid was linoleic (57.72–63.11%), followed by oleic acid (19.37–21.79%), linolenic acid (0.23–1.10%), palmitic acid (12.47–15.06%) and stearic acid (2.56–4.10%).…”
Section: Chemical Characterization Of the Prickly Pear Seed Oilmentioning
confidence: 99%
See 2 more Smart Citations